A fixed solid sphere with radius R and charge density given by ρ ( r ) = r 2 ρ 0 is placed at a distance 2 d from a fixed particle with charge q (from the center of the sphere). If at a distance x from the fixed particle there is a point charge at equilibrium, then x can be written as b π R ρ 0 + q a d q .
Find the value of a + b .
Assume both of the fixed charges are of the same sign.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution. I believe there should be one more condition, that the charged sphere should also have same charge sign as the 2 particles. Otherwise, the second particle has to be on the other side of the sphere, and the distance between them would be 2d+x, not 2d-x. Then in the final answer, the denominator would have a "-" instead of "+".
Log in to reply
Yes. u r right.But I assumed this from the the format of answer given. In this format, q and ρ 0 are in square root. So they can't be negative. In this way I have assumed. But even then they must be indicated.
As the particle is at equillibrium the net force is 0 . But the only forces acting are depending on the elcectric field which generates each fixed charge, which will have an opposite sign without depending on the sign of the charge we put between the fixed charges, so we expect that both of the electric fields are equal in magnitude:
By using Gauss' law: ∮ E q d s = ϵ 0 q ⇒ E q = 4 π x 2 ϵ 0 q ∮ E s d s = ϵ 0 ∫ 0 2 π ∫ 0 π ∫ 0 R r 2 ρ 0 r 2 s i n ( ϕ ) d r d ϕ d θ E s = 4 π ( 2 d − x ) 2 ϵ 0 4 π R ρ 0
As they're equal in magnitude: 4 π ( 2 d − x ) 2 ϵ 0 4 π R ρ 0 = 4 π x 2 ϵ 0 q ( 2 d − x ) 2 4 π R ρ 0 = x 2 q 2 π R ρ 0 x = q ( 2 d − x ) x = 2 π R ρ 0 + q 2 d q
Problem Loading...
Note Loading...
Set Loading...
As charge density of sphere is ρ ( r ) = r 2 ρ 0
So d V d q = r 2 ρ 0
d q = r 2 ρ 0 d r d V ∗ d r
d q = r 2 ρ 0 ∗ 4 π r 2 d r
d q = 4 π ρ 0 d r
Q = 4 π ρ 0 R
So in equillibrium,
( 2 d − x ) 2 k Q = ( x ) 2 k q
2 d − x Q = x q
On solving,
x ( Q + q ) = 2 d q
x = Q + q 2 d q
x = 2 π ρ 0 R + q 2 d q
So a = b = 2 ⇒ a + b = 4 .